Aortic Root Enlargement during Aortic Valve Replacement in Adults - Furman, Miroslav M.; Varbanets, Sergey V.; Dovgan, Oleksandr M. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Aortic valve replacement is a gold standard in the treatment of patients with severe aortic stenosis or combined aortic pathology. However, aortic valve pathology is often associated with a narrow aortic orifice, particularly in patients with severe aortic stenosis. In 1978, Rahimtoola first described the term of prosthesis-patient mismatch. He noted that effective orifice area of the prosthesis is smaller than that of the native valve. To minimize this complication, there are several surgical strategies: aortic root enlargement (ARE), implantation of a frameless biological prosthesis in the native position, neocuspidalization procedure, Ross procedure, aortic root replacement with xenograft or homograft. ARE is an excellent option, however, some authors outline additional perioperative risks. The aim. To analyze immediate results of ARE during isolated aortic valve replacement and in cases when it is combined with other heart pathologies. Materials and methods. Our study included 63 patients who underwent ARE. Isolated aortic valve replacement was performed in the majority of cases, but often aortic root replacement procedure was combined with coronary artery bypass grafting. Results and discussion. One of 63 patients died (hospital mortality 1.6%) at an early hospital stage (30 postoperative days). Measurement of the aortic valve ring was performed by two methods, through preoperative echocardiography and perioperative measurement using a valve sizer. However, perioperative dimension was chosen as the basis for the calculations. In 62 patients, the perioperative diameter of the aortic valve ring ranged from 19 to 23 mm, only one patient had a diameter of 24 mm. According to our findings, ARE enabled to achieve an average aortic ring size increase of 2.68 cm2 (from 1.5 to 3.4 cm2) and to prevent prosthesis-patient mismatch in 42 (66.7%) cases. Conclusions. Prosthesis-patient mismatch is considered a serious complication in the postoperative period. Narrow aortic root is a common pathology that should be considered during surgery. ARE is a safe procedure and is not associated with an increased risk of mortality and complications.